PROS AND CONS OF ANGKATAN 66: IMPLEMENTATION OF THE CONCEPT OF UNIVERSAL HUMANISM BY H.B. JASSIN IN THE PERIODIZATION OF INDONESIAN LITERARY HISTORY - Ikhlas, Ahmad Muh. (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study explores the principles of universal humanism initiated by H.B. Jassin, a prominent Indonesian literary critic, in the formulation of the Periodization of Modern Indonesian Literary History, especially Angkatan 66 (the 66th Class). Jassin is one of the figures who strongly opposes the subjugation of literature by certain ideologies or political groups. On the other hand, he also involved the principles of universal humanism that were politically accused of being the basis of literary history, a consideration that in turn triggered criticism of him. Based on a literature review, this historical study concludes that Jassin's decision to embed universal humanism with strong political nuances in the mapping of modern Indonesian literary history is closely related to the turbulent socio-political context of Indonesia at that time. For Jassin, the relationship between socio-political activities, universal humanism and literature is an interdependent and legitimizing relationship, not a hierarchy. In addition, the emergence of Angkatan 66 in the Periodization of the History of Modern Indonesian Literature reflects the same orientation between socio-political activities and the principles of universal humanism, namely freedom and resistance to oppression.